Fatores psicológicos, níveis de alfa-amilase salivar e Líquen Plano Bucal: um estudo de caso-controle - Simoura, Juliana Araujo da Silva (2017)
Introduction: Lichen planus is a chronic inflammatory disease of uncertain etiology that can affect the skin and/or mucous membranes, especially the oral mucosa. Objective: To evaluate psychological (anxiety, depression and stress) and salivary (flow and levels of salivary alpha amylase) factors in individuals with oral lichen planus. Materials and Methods: An exploratory control case study was conducted. The case group consisted of 23 individuals with clinical and histopathological diagnosis of oral lichen planus, matched by sex and age to a control group, with an equal number of healthy individuals, from the same population that originated the cases. The population underwent clinical examination of the oral cavity, psychological tests (perceived stress scale and Beck depression and anxiety inventories) and saliva collection to determine the salivary flow and alpha-amylase levels at three moments along the day (on waking, thirty minutes after waking and before bed). The data were analyzed statistically. The Odds Ratio and its 95% confidence interval were computed. The McNemar χ2 test was used, considering a significance level of 5%. For quantitative variables, the Mann-Whitney test was used to compare the medians of salivary flow, alpha amylase response on waking, and salivary alpha amylase levels at each of the collection times, between cases and controls. The Friedman test was applied to evaluate the concentration of the alpha amylase from each of the three moments of saliva collection throughout the day. Spearman's correlation coefficient was computed to determine correlation between alpha amylase concentration and the test scores of stress, anxiety, depression, and salivary flow. Results: There was a significant correlation between anxiety, depression, stress and LPB, and between stress and α-AS decline. Higher levels of salivary alpha amylase were found in the case group in the second collection time when compared to controls. Conclusion: The applied psychological tests indicated that factors such as stress, anxiety and depression were correlated to oral lichen planus. Salivary analyses demonstrated a higher concentration of alpha amylase thirty minutes after waking on individuals with the disease, suggesting the role of alpha amylase as a promising biomarker for further longitudinal studies on the subject.